Relationship between Dyskerin Expression and Telomerase Activity in Human Breast Cancer - Lorenzo Montanaro; Maria Calienni; Claudio Ceccarelli; Donatella Santini; Mario Taffurelli; Stefano Pileri; Davide Treré; Massimo Derenzini (Cellular Oncology)
The nucleolar protein dyskerin is involved in the modification of specific uridine residues to pseudouridine on ribosomal and small nuclear RNAs and in the stabilization of the telomerase RNA component (TERC). In this study we investigated for the first time the relationship between dyskerin expression and telomerase activity in a series of 61 primary breast carcinomas. We found that when dyskerin mRNA values were very low the telomerase activity was markedly reduced, independently of the expression of other important components of the telomerase complex such as telomerase reverse transcriptase (TERT). In vitro experiments showed that reduction of dyskerin expression affect telomerase activity through the reduction of TERC. Only when TERC levels were strongly reduced telomerase activity was hindered. Retroviral mediated over-expression of TERC abolished the telomerase impairment due to dyskerin knock down. In conclusion, our results indicated that, beside its effect on ribosome biogenesis, the levels of dyskerin in cancer cells modulate telomerase activity through the regulation of TERC levels, independently of TERT expression. This should be taken into consideration when utilizing TERT expression as a surrogate indicator of telomerase activity in tumour pathology.